2011
DOI: 10.1017/s0007114511003606
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the design, conduct and reporting of human intervention studies to evaluate the health benefits of foods

Abstract: There is substantial evidence to link what we eat to the reduction of the risk of major chronic diseases and/or the improvement of functions. Thus, it is important for public health agencies and the food industry to facilitate the consumption of foods with particular health benefits by providing consumer products and messages based on scientific evidence. Although fragmentary advice is available from a range of sources, there is a lack of comprehensive scientific guidelines for the design, conduct and reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 28 publications
0
90
0
1
Order By: Relevance
“…Unfortunately it is not possible to administer an intervention trial based on counselling as a double-blind experiment in order to conclude that any difference that develops between the groups is directly caused by the factor under investigation [39]. It is therefore of great importance to evaluate the compliance when evaluating the effect of dietary counselling.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately it is not possible to administer an intervention trial based on counselling as a double-blind experiment in order to conclude that any difference that develops between the groups is directly caused by the factor under investigation [39]. It is therefore of great importance to evaluate the compliance when evaluating the effect of dietary counselling.…”
Section: Discussionmentioning
confidence: 99%
“…The review was conducted in accordance with established guidelines for systematic reviews specific to human intervention studies in nutritional science (64). Eligible study designs were prospective studies (including cohorts and randomized controlled trials) published in English language that reported quantitative data for LCv-3PUFAs (dietary intake, supplemental intake, or biomarker status).…”
Section: Literature Search and Study Inclusionmentioning
confidence: 99%
“…Dietary intervention studies are time-and resource-heavy, particularly when clinical endpoints are required (47) .…”
Section: Observational V Intervention Studiesmentioning
confidence: 99%